1954
DOI: 10.1001/archinte.1954.00250020082005
|View full text |Cite
|
Sign up to set email alerts
|

Roentgen Changes Observed in Generalized Scleroderma

Abstract: (Table 2). RESULTSFor the purpose of presentation the positive roentgen findings have been divided into the following groups: findings involving gastrointestinal tract, bones and joints, soft tissues, and cardiovascular system and hepatic or splenic enlargement or both. We were impressed by the high incidence of positive roentgen findings in these systems

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1
4

Year Published

1958
1958
1985
1985

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 3 publications
0
5
1
4
Order By: Relevance
“…A delay in oesophageal transit time when the subject is in the recumbent position, and inability to swallow against gravity, were observed radiologically in systemic sclerosis by Kure, Yamagata, Tsukada, and Hiyoshi (1936), Lindsay, Templeton, and Rothman (1943), Hale and Schatzki (1944), Olsen, O'Leary, and Kirklin (1945), Mahrer, Evans, and Steinberg (1954), and Boyd, Patrick, and Reeves (1954). The manometric studies of Kramer and Ingelfinger (1949) and of Dornhorst, Pierce, and Whimster (1954) confirmed the impairment or complete absence of oesophageal peristalsis in many patients with systemic sclerosis.…”
mentioning
confidence: 90%
“…A delay in oesophageal transit time when the subject is in the recumbent position, and inability to swallow against gravity, were observed radiologically in systemic sclerosis by Kure, Yamagata, Tsukada, and Hiyoshi (1936), Lindsay, Templeton, and Rothman (1943), Hale and Schatzki (1944), Olsen, O'Leary, and Kirklin (1945), Mahrer, Evans, and Steinberg (1954), and Boyd, Patrick, and Reeves (1954). The manometric studies of Kramer and Ingelfinger (1949) and of Dornhorst, Pierce, and Whimster (1954) confirmed the impairment or complete absence of oesophageal peristalsis in many patients with systemic sclerosis.…”
mentioning
confidence: 90%
“…For ease of discussion, radiographic abnormalities were classified into three broad categories: Category Z : Findings suggesting the presence of an inflammatory arthropathy: juxtaarticular demineralization, joint space narrowing, erosive changes, or ankylosis. Category ZZ: A, Common, well recognized findings generally regarded as typical for classic PSS: soft tissue atrophy, subcutaneous calcinosis, digital tuft resorption, digital flexion contractures, or generalized osteopenia (19)(20)(21)(22)(23). B, Previously reported uncommon or rare findings including: subluxations (1 1); periostitis (1 1,24); resorptive changes of superior margins * Although none of the 10 CREST patients met the major classification criterion for PSS, it is of interest that 9 of these patients fulfilled the proposed ARA minor criteria requirements for definite scleroderma (i.e., the presence of two or more of the following: sclerodactyly, digital pitting scars, and roentgenographic bibasilar pulmonary fibrosis).…”
mentioning
confidence: 99%
“…Hepatomegaly (Rivelis, 1963) and hepatosplenomegaly (Milbradt, 1934;Boyd et al, 1954;Massimo, 1954) have been noted, as well as cirrhosis (Piper and Helwig, 1955;Calvert et al, 1958;Perez and Barbieri, 1959) and "chronic biliary cirrhosis" (Goetz, 1945). Striking calcification of the liver and spleen has been recorded once (Harvier and Bonduelle, 1947).…”
Section: Discussionmentioning
confidence: 99%